Ultralow Ru Incorporated Amorphous Cobalt‐Based Oxides for High‐Current‐Density Overall Water Splitting in Alkaline and Seawater Media. Issue 39 (12th August 2021) - Wu, Dulan; Chen, Ding; Zhu, Jiawei; Mu, Shichun
Abstract: Realizing efficiency and stable hydrogen production by water electrolysis under high current densities is essential to the forthcoming hydrogen economy. However, its industrial breakthrough is seriously limited by bifunctional catalysts with slow hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) electrocatalytic processes. Herein, an ultralow Ru incorporated amorphous cobalt‐based oxide (Ru‐CoOx /NF), effectively driving the electrolysis of water at high current densities in alkaline water and seawater, is designed and constructed. In 1 m KOH, to reach the current density of 1000 mA cm −2 for HER and OER, it only needs 252 and 370 mV overpotentials, respectively, beyond commercial Pt/C and RuO2 catalysts. At the high current density, it also presents outstanding electrochemical stability. Then the electrolyzer apparatus assembled with Ru‐CoOx /NF, just requires the ultra‐low voltage of 2.2 and 2.62 V to support the current density of 1000 mA cm −2 in alkaline water and seawater electrolysis, respectively, for hydrogen production, better than that of the commercial Pt/C and RuO2 catalysts. This work demonstrates that Ru‐CoOx /NF is one of the most promising catalysts for industrial applications and provides a possibility for exploration of high‐current‐density water electrocatalysis by changing the crystallinity of the catalyst. Abstract : To deliver the alkaline water and seawater at high current densities, the electrolyzer with Ru‐CoOx /NF || Ru‐CoOx /NF only requires the ultralow voltage compared to commercial Pt/C/NF || RuO2 /NF, accompanying the nearly 100% Faraday efficiency and excellent electrochemical stability, which depends on its unique amorphous structure. This study provides a new idea for the development of catalysts toward industrial water electrolysis.